2017
DOI: 10.18632/oncotarget.22146
|View full text |Cite
|
Sign up to set email alerts
|

Increased Jab1/COPS5 is associated with therapeutic response and adverse outcome in lung cancer and breast cancer patients

Abstract: Adjuvant chemotherapy has been established as standard treatment for advanced cancer among multidisciplinary therapies. A simple and instructive biomarker for therapeutic response and recurrence is needed to evaluate the therapeutic effect. Jab1/COPS5 level has been shown to be associated with tumor progression and poor outcomes in many types of cancer patients. This study aims to further evaluate the clinical and prognostic value of Jab1/COPS5 level as a biomarker in lung and breast cancer patients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Recently, we retrospectively collected and analyzed data of 88 lung cancer and 76 breast cancer patients, and found that lung cancer patients with higher Jab1 level was less responsive to chemotherapy. Recurrent breast cancer patients had much higher Jab1 level (Hou et al, 2017 ). Both breast cancer patients and lung cancer patients with higher Jab1 level had significantly shorter disease-free survival and overall survival.…”
Section: Jab1/cops5 As Biomarker For Diagnostic and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we retrospectively collected and analyzed data of 88 lung cancer and 76 breast cancer patients, and found that lung cancer patients with higher Jab1 level was less responsive to chemotherapy. Recurrent breast cancer patients had much higher Jab1 level (Hou et al, 2017 ). Both breast cancer patients and lung cancer patients with higher Jab1 level had significantly shorter disease-free survival and overall survival.…”
Section: Jab1/cops5 As Biomarker For Diagnostic and Prognosismentioning
confidence: 99%
“…Both breast cancer patients and lung cancer patients with higher Jab1 level had significantly shorter disease-free survival and overall survival. In a multivariate survival analysis, Jab1 was correlated with disease-free survival and overall survival in breast cancer (Hou et al, 2017 ). The Jab1 level was found to be a possible biomarker for clinical response to chemotherapy in lung cancer patients and for postoperative relapse in breast cancer patients who received adjuvant chemotherapy (Hou et al, 2017 ), indicating that Jab1 predicts treatment response in lung cancer and relapse in breast cancer patients.…”
Section: Jab1/cops5 As Biomarker For Diagnostic and Prognosismentioning
confidence: 99%
“…Changed genes in any cancer, including breast cancer, reflect the biological diversity of cellular phenotype and physiological function and could become important research areas for elucidating molecular mechanisms. Already, many studies have found genes or proteins strongly associated with the progress and prognosis of breast cancer, including enhancer of zeste 2 (EZH2) polycomb repressive complex 2 subunit [20] and Jab1/COPS5 [21]. In addition, the nuclear receptor-interacting protein 1 (NRIP1) and the MAPK signaling pathway can regulate the development of breast cancer cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…The role of CAV1 in gastric cancer remains controversial 33 . The oncogenic role of COPS5 34 , MRE11 35 , RICTOR 36 , CHEK1 37 , CLDN7 38 , EIF4EBP1 39 , EPPK1 40 , ITGA2 41 , MAP2K1 42 , RPS6KA1 43 , TFRC 44 have been reported in different cancer types. Specifically EIF4EBP1 were overexpressed in GC 45 and MAP2K1 has been identified to be associated with GC by different studies 46 .…”
Section: Discussionmentioning
confidence: 99%